Inventar der Befehle des Obersten Chefs der Sowjetischen Militäradministration in Deutschland (SMAD) 1945–1949. - Offene Serie - - Foitzik, Jan 1948- (Texte und Materialien zur Zeitgeschichte, 1994)
For the first time the open orders of the highest chief of the SMAD arecompletely compiled in this inventory. Now one can realize the degree ofdependence of the German administration and political organizations in the SBZ on the orders of the SMAD. In a detailed introduction the organization andstructure of the orders and the relationship with the parties especially withthe KPD/SED are described. The following orders are chronologically arranged